Gender representation of characters in Palanca Award winning short stories for children 1989-2004 - Dery, Zipporah M. (2005)
Children's literature is very significant in one's development. Children could learn how to perceive themselves as well as the objects around them from the books they read. They could also project themselves in the character involved in the material and relate the persona's gender and pursuit or interest with reference to them and their own gender. Since children's literature could influence one's understanding of the world as well as gender development, it is significant to observe how characters in such materials are portrayed according to their gender and find out if equal gender representation is present.